THE EFFECT OF PH ON THE RESISTANCE OF PROTEUS MIRABILIS BACTERIA TO ANTIBIOTICS - Soltan, Zahraa Majed Ali; Safy, Shahlaa Ali Mardan; Kariz , Wijdan Rahim Abed; Obaid, Yasser Ammar Hussein; Hussein, Saja Abbas Burhi (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Twenty-six bacterial isolates of Proteobacteria were isolated from patients with urinary tract infections from several hospitals in Babylon province. Urine samples were collected from patients with urinary tract infections, then these samples were grown on different culture media and identified by several biochemical tests. Also, their drug sensitivity was studied using nine types of antibiotics. The drug sensitivity of these samples was studied at acidic, neutral and basic pH using disk diffusion method. The study showed that ciprofloxacin and azithromycin had high activity against bacteria at both acidic and neutral pH, while amikacin, meropenem, imipenem and ciprofloxacin had high activity at basic pH against these bacteria